Structures and hydrogen bonding recognition of mefenamic acid form I crystals in mefenamic acid/ethanol solution - Abdul Mudalip, Siti Kholijah; Abu Bakar, Mohd Rushdi; Adam, Fatmawati; Jamal, Parveen (IACSIT Press, 2013)
Mefenamic acid is one of the active pharmaceutical ingredients that exhibit polymorphism. An experimental study has found that Form I of mefenamic acid is produced from cooling crystallization with ethanol as a solvent. Hydrogen bonding is considered as the fundamental factor that controls the polymorphism of mefenamic acid in ethanol. This work, in essence, was performed to verify this using molecular dynamics simulation.The simulation was performed using COMPASS force field available in Material Studio package.The result of the simulation showed strong hydrogen bonding between oxygen and hydrogen in the carboxylic group. The results of the Fourier transform infrared spectroscopy analysis confirmed the existence of O-H, C-O and C=O bonds. These findings proved the presence of hydrogen bonds that leads to the formation of hydrogen motif in Form I of mefenamic acid during crystallization process using ethanol as a solvent.